2020
DOI: 10.3390/molecules25051102
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng Gintonin Contains Ligands for GPR40 and GPR55

Abstract: Gintonin, a novel ginseng-derived glycolipoprotein complex, has an exogenous ligand for lysophosphatidic acid (LPA) receptors. However, recent lipid analysis of gintonin has shown that gintonin also contains other bioactive lipids besides LPAs, including linoleic acid and lysophosphatidylinositol (LPI). Linoleic acid, a free fatty acid, and LPI are known as ligands for the G-protein coupled receptors (GPCR), GPR40, and GPR55, respectively. We, herein, investigated whether gintonin could serve as a ligand for G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Gintonin is a novel lysophosphatidic acid (LPA)–ginseng protein complex naturally derived from ginseng . It contains an exogenous G-protein-coupled lysophosphatidic acid receptor (LPAR) ligand capable of repressing inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Gintonin is a novel lysophosphatidic acid (LPA)–ginseng protein complex naturally derived from ginseng . It contains an exogenous G-protein-coupled lysophosphatidic acid receptor (LPAR) ligand capable of repressing inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating LPA and LPI are known to bind the specific GPCRs LPA and GPR55 receptor, respectively, and elicit various cellular responses [36]. Although limited studies to date have focused on the intracellular effects of simultaneous activity of the two ligands, studies on gintonin, a ginseng-derived glycolipoprotein complex containing LPA and LPI, report possible crosstalk between the two receptors [37].…”
Section: Discussionmentioning
confidence: 99%
“… 37 Recently, it was demonstrated that gintonin linoleic acid and LPI interact with GPR40 and GPR55 to exhibit cellular effects such as insulin secretion and Ca 2+ -mediated cell migration, respectively. 49 Thus, gintonin contains at least three different ligand complexes for G protein-coupled receptor regulation such as LPA receptors, GPR40, and GPR55 ( Fig. 2 ).…”
Section: Characteristics Of the Lipid Components Of Gintonin And Gefmentioning
confidence: 99%
“… 49 Interestingly, although the signaling pathways of GPR40 are different from that of LPA receptors, 49 LPA receptors and GPR55 share common signaling pathways, in that activation of both receptors elicits [Ca 2+ ] i transients and induces Ca 2+ -dependent cell migration. 49 Gintonin-mediated activation of GPR55 and LPA receptors is coupled to [Ca 2+ ] i transients through Gα q/11 activation-phospholipase C activation-IP 3 formation-[Ca 2+ ] i transient induction. Thus, gintonin produces second messenger Ca 2+ via LPA receptors and GPR55.…”
Section: Characteristics Of the Lipid Components Of Gintonin And Gefmentioning
confidence: 99%
See 1 more Smart Citation